Nuclear Ca2+-Calmodulin signaling in cardiac myocytes reduces catecholamine-evoked protein translation and prevents hypertrophy - Riedel, Anja; Medert, Rebekka; Monaco, Sara; Gjerga, Enio; Tolksdorf, Xenia; Richter, Christin; Malz, Michelle; Schrader, Meike; Kuryshev, Vladimir; Busch, Martin; Jungmann, Andreas; Löwenthal, Zoe; et al. (Cell calcium, 2026)
Cardiac remodeling, including hypertrophy, is associated with alterations in cytosolic Ca2+ homeostasis of cardiac myocytes that spill over into the nucleoplasm. To test whether nuclear Ca2+ signaling acts causally on the development of cardiac hypertrophy, we expressed parvalbumin to buffer nuclear Ca2+ and we blocked nuclear Ca2+-calmodulin signaling by Adeno-associated virus (AAV)-mediated expression of the calmodulin (CaM) binding-peptide nlsCaMBP4, respectively, in the nuclei of ES cell-derived (Cor.At) and neonatal rat ventricular cardiac myocytes (NRVCM). Expression of nlsCaMBP4, but not parvalbumin, leads to a significant reduction of hypertrophic growth induced by phenylephrine (PE). Expression of nlsCaMBP4 did not alter the amplitude of electrically-evoked intracellular Ca2+ transients in NRVCMs in the absence or presence of PE, and did not affect the PE-evoked increase in store-operated Ca2+ entry. Transcriptome analysis on NRVCMs expressing nlsCaMBP4 revealed that induction of classical hypertrophy markers such as ANF and BNP or MEF2 target genes (such as Srpk3, Xirp1 and Xirp2) were not reduced by nlsCaMBP4 expression. Further analysis of the nuclear Ca2+-calmodulin-regulated gene pool revealed differential expression of genes involved in mRNA translation, including the translation initiation factor subunits Eif2s1, Eif3d and Eif5, whose upregulation was absent in nlsCaMBP4-treated myocytes. Puromycin assays showed that inhibition of Ca2+-calmodulin signaling prevented catecholamine-evoked protein translation, suggesting that Ca2+-calmodulin signaling in the nucleus of cardiac myocytes regulates translation via transcriptional control mechanisms. However, future studies are needed to identify the exact molecular components and machinery that integrate Ca2+-calmodulin-dependent regulation of transcription, protein translation, and development of cardiac myocyte hypertrophy.